Push-Pull Converter Fed Three-Phase Inverter for Residential and Motor Load - Samuel Rajesh Babu (Institute of Advanced Engineering and Science, 2015)
The proposed paper is an new approach for power conditioning of a PV (photo-voltaic) cell array. The main objective is to investigate an approach to provide and improve the delivered electric energy by means of power conditioning structures with the use of alternative renewable resources (ARRs) for remote rural residential or industrial non-linear loads. This approach employs a series-combined connected boost and buck boost DC-DC converter for power conditioning of the dc voltage provided by a photo-voltaic array. The input voltage to the combined converters is 100 V provided from two series connected PV cells, which is converted and increased to 200 V at the dc output voltage. Series-combined connected boost and buck-boost DC-DC converters operate alternatively. This helps to reduce the input ripple current and provide the required 400 Vdc on a sinusoidal PWM three-phase inverter. Analysis of the two series-combined DC-DC converters is presented along with simulation results. Simulations of the series-combined DC-DC converters are presented with an output DC voltage of 200 V and a maximum output load of Po = 600 W.